2016
DOI: 10.1155/2016/2573476
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Subcapsular Renal Hematoma: Strange Case in an Anticoagulated Patient with HWMH after Aortic and Iliac Endovascular Stenting Procedure

Abstract: Spontaneous subcapsular renal hematoma is a rare condition in clinical practice. It is caused by renal cysts, benign and malignant renal tumors, vascular lesions, and antiplatelet or anticoagulant therapy. In this paper we report an unusual case of rupture of a renal cyst of a 66-year-old male patient during an aortic and iliac endovascular procedure for a massive calcified atheroma above the iliac bifurcation. We suspected that the bolus of high weight molecular heparin given during the procedure caused the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…The use of anticoagulant therapy is also another cause that has been reported to trigger these bleeds. [3] Interestingly, on review of literature, we found only one case report of a spontaneous perinephric hematoma developing secondary to the use of a NOAC, namely dabigatran. [6] Our case had a similar history of prior use of a NOAC, apixaban for paroxysmal atrial fibrillation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The use of anticoagulant therapy is also another cause that has been reported to trigger these bleeds. [3] Interestingly, on review of literature, we found only one case report of a spontaneous perinephric hematoma developing secondary to the use of a NOAC, namely dabigatran. [6] Our case had a similar history of prior use of a NOAC, apixaban for paroxysmal atrial fibrillation.…”
Section: Discussionmentioning
confidence: 91%
“…These bleeds are classically described to present in the form of Lenk's triad with acute flank pain, flank mass and hypovolemic shock. [1] Whilst some of these hematomas are reported to occur spontaneously, [1] secondary causes such as renal tumors, [2] the use of anticoagulant therapy [3] and procedural complications of renal biopsy [4] are also frequently reported. Amongst renal tumors, angiomyolipomas and renal cell carcinomas are known to be most frequently associated with perinephric hematomas.…”
Section: Introductionmentioning
confidence: 99%
“…5 Other factors include anticoagulation, nonsteroidal anti-inflammatory drugs, cystic diseases, blood dyscrasia, hypertension, hemodialysis, post-lithotripsy, or ureterorenoscopy. 6,7…”
Section: Discussionmentioning
confidence: 99%
“…Renal pelvic haematomas usually present in patients with pre-existing renal pathology such as renal stones, cancer or in the setting of trauma. 4 Having a non-traumatic spontaneous pelvic haematoma in a patient who is otherwise fit and well is very rare with only a few reported cases in the literature. There have been reported cases of large renal pelvis haematomas in uretero-pelvic junction obstruction presenting as an acute abdomen.…”
Section: Discussionmentioning
confidence: 99%